IDENTIFIKASI FAKTOR PENYEBAB WASTE KONSTRUKSI DENGAN MENGGUNAKAN PENDEKATAN LEAN CONSTRUCTION (STUDI KASUS: PROYEK X KABUPATEN KAPUAS) - Maulana, Doni Rahman (INFO-TEKNIK, 2024)
Waste is a problem that often occurs in construction projects. Waste is an activity that utilizes resources but does not produce the expected added value. Waste can be eliminated with a lean approach where this approach is carried out by identifying and eliminating waste so that it can meet customer value. Therefore, it is necessary to identify waste, in this study to identify the factors causing the occurrence of construction waste in the rehabilitation and improvement of irrigation networks in the working area of block A, Kapuas Regency. There were 9 variables with 43 indicators of factors causing waste which became the basis for this research. The method used was the Borda method to get the factors causing the most frequent waste and also the severity index method to get the main factors causing the occurrence of waste. The results of this study are the waste that most often occurs, namely the planning error factor with a weight value of 0.031 and the main factor for the occurrence of waste, namely the planning error factor with an SI probability weight of 46.7% including category C (Enough) with a value of 3 while the SI impact weight is 65% belongs to category B (Large) with a value of 4